2016
DOI: 10.1177/2056305116680004
|View full text |Cite
|
Sign up to set email alerts
|

Social Networking Site Behaviors Across the Relational Lifespan: Measurement and Association With Relationship Escalation and De-escalation

Abstract: Social networking sites (SNSs) have become a ubiquitous aspect of daily life. Millions of people log in on a daily basis to connect and share their lives through photos and posts (e.g., Duggan, 2015). The accessibility of information on SNS influences relationship development over time, aids in relationship maintenance, displays relationship dissolution, and reveals the multimodality of information between (online and offline) relationships (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Given these affordances, it is unsurprising that several studies have shown that SNSs are commonly used to monitor romantic partners or ex-partners (e.g., Brody, LeFebvre, & Blackburn, 2016;Dainton & Stokes, 2015;Fox & Tokunaga, 2015;Marshall, Bejanyan, Di Castro, & Lee, 2013;Robards & Lincoln, 2016;Tokunaga, 2011). Because SNSs allow both self-generated and other-generated information to be tied to one's profile via posting, tagging, geo-location, and sharing, there are multiple sources of information conveniently amalgamated in one easily accessible location.…”
Section: Partner Monitoring and Information Seeking On Snssmentioning
confidence: 99%
“…Given these affordances, it is unsurprising that several studies have shown that SNSs are commonly used to monitor romantic partners or ex-partners (e.g., Brody, LeFebvre, & Blackburn, 2016;Dainton & Stokes, 2015;Fox & Tokunaga, 2015;Marshall, Bejanyan, Di Castro, & Lee, 2013;Robards & Lincoln, 2016;Tokunaga, 2011). Because SNSs allow both self-generated and other-generated information to be tied to one's profile via posting, tagging, geo-location, and sharing, there are multiple sources of information conveniently amalgamated in one easily accessible location.…”
Section: Partner Monitoring and Information Seeking On Snssmentioning
confidence: 99%
“…People often create digital objects (such as tweets, photos, or comments) to help their future selves remember what it was like when it occurred (Humphreys, 2018). Specifically, researchers have argued that virtual possessions (e.g., the online, digital items and artifacts that individuals and couples create and retain throughout their relationship) have the potential to change the way people form memories of their relationships (Brody et al, 2016;Konrad et al, 2016) and even alter relationship processes (Fox et al, 2013(Fox et al, , 2014LeFebvre et al, 2015). For instance, LeFebvre and colleagues (2015) examined the relationship dissolution model (RDM; see Duck, 1982;Rollie & Duck, 2006), suggesting that it may be reshaped or altered to highlight the processes individuals often experience during the breakup process.…”
mentioning
confidence: 99%
“…For example, Fox et al (2013) explored Facebook’s role in Knapp’s (1978) five-stage model, with particular attention to the implications of publicly declaring “in a relationship.” LeFebvre and her colleagues (2015) extended Rollie and Duck’s (2006) model of offline relationship dissolution to online environments, and showed that Facebook’s affordances allow relational partners to amplify and alter different aspects of offline relationship dissolution. Similarly, Brody et al (2016) applied Knapp and Vangelisti’s (2010) stage model to online behaviors, suggesting that these behaviors are associated with relationships’ quality and adjustment. Sharabi and Hopkins (2021) applied the investment model to Instagram to better understand relationship maintenance and attention to alternatives by couples using a highly visual platform.…”
Section: Offline Construction Of Romantic Relationships: Knapp’s Modelmentioning
confidence: 99%
“…Many of these studies examine the role of social media across the relational lifespan (Brody et al, 2016; Fox et al, 2013, 2014) while others focus on specific stages to explore the ways people fall in love, maintain their relationships, or break up online (Brody et al, 2020; Fox & Tokunaga, 2015; Fox & Warber, 2013; Tong, 2013). A common theme among these studies is the application of offline relationship models to social media (Brody et al, 2016; Fox et al, 2013; LeFebvre et al, 2015; Sharabi & Hopkins, 2021), often through a focus on the role of specific affordances (Frampton & Fox, 2018; LeFebvre et al, 2015; Tokunaga, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation